2003
DOI: 10.1038/sj.onc.1206220
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive immunization using highly metastatic human tumor cells identifies SIMA135/CDCP1, a 135 kDa cell surface phosphorylated glycoprotein antigen

Abstract: We have previously used a subtractive immunization (SI) approach to generate monoclonal antibodies (mAbs) against proteins preferentially expressed by the highly metastatic human epidermoid carcinoma cell line, M + HEp3. Here we report the immunopurification, identification and characterization of SIMA135/CDCP1 (subtractive immunization M + HEp3 associated 135 kDa protein/CUB domain containing protein 1) using one of these mAbs designated 41-2. Protein expression levels of SIMA135/CDCP1 correlated with the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 35 publications
6
174
1
Order By: Relevance
“…Consistent with CDCP1 having a role in sphere formation, western blot analysis showed that CDCP1 levels were markedly higher in SFCs compared with NSFCs ( Figure 5b, non-adhered). In addition, analysis of Akt, Src and ERK (extracellular-signal-regulated kinase) pathways that are important in CDCP1-mediated signaling, 18,20,[23][24][25] demonstrated that each is activated in SFCs compared with NSFCs ( Figure 5b, non-adhered). Interestingly, when both SFCs and NSFCs were replated onto cell culture dishes for adherent growth, levels of CDCP1 and activation of Akt, Src and ERK returned to basal levels (Figure 5b, adhered).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with CDCP1 having a role in sphere formation, western blot analysis showed that CDCP1 levels were markedly higher in SFCs compared with NSFCs ( Figure 5b, non-adhered). In addition, analysis of Akt, Src and ERK (extracellular-signal-regulated kinase) pathways that are important in CDCP1-mediated signaling, 18,20,[23][24][25] demonstrated that each is activated in SFCs compared with NSFCs ( Figure 5b, non-adhered). Interestingly, when both SFCs and NSFCs were replated onto cell culture dishes for adherent growth, levels of CDCP1 and activation of Akt, Src and ERK returned to basal levels (Figure 5b, adhered).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative densitometric analysis showed a shift from only ~20% of CDCP1 being present in lipid raft-poor fraction 4 from unstimulated Caov3, to about 65% in EGF-stimulated cells. As the kinase Src, which is the key mediator of tyrosine phosphorylation of CDCP1 (7,14,32), is found in lipid rafts and differentially signals within and outside these structures (33), we were interested to examine the impact of EGF on phosphotyrosine-CDCP1 (pY-CDCP1). CaOV3 and OVCA420 cells were incubated with EGF for 6, 12 and 24 h before immunoprecipitation of CDCP1 and detection of pY-CDCP1 using an anti-phosphotyrosine antibody.…”
Section: Egf Reduces Cdcp1 Palmitoylation and Promotes Its Redistribumentioning
confidence: 99%
“…Complement C1r/C1s, Uegf, Bmp1 (CUB) domaincontaining protein 1 (CDCP1), also described as SIMA135 and TRASK (1,2), is a type 1 transmembrane protein with 3 CUB domains as the extracellular domains and several tyrosine residues that can be phosphorylated by Src family kinases (SFK) in the intracellular domain (1)(2)(3)(4)(5)(6). The expression of CDCP1 was reported in several human malignancies, such as colon and breast cancers (3,7).…”
Section: Introductionmentioning
confidence: 99%